Deficiency of IKKα in Macrophages Mitigates Fibrosis Progression in the Kidney after Renal Ischemia-Reperfusion Injury - Feng Zhang; Li Fan; Hao Zhang; Wen-juan Huang; Dong Sun; Bin-bin Pan; Xin Wan; Chang-Chun Cao (Journal of Immunology Research)
Aims. Acute kidney injury (AKI) can lead to chronic kidney disease (CKD), and macrophages play a key role in this process. The aim of this study was to discover the role of IκB kinase α (IKKα) in macrophages in the process of AKI-to-CKD transition. Main Methods. We crossed lyz2-Cre mice with IKKα-floxed mice to generate mice with IKKα ablation in macrophages (Mac IKKα-/-). A mouse renal ischemia/reperfusion injury (IRI) model was induced by clamping the renal artery for 45 minutes. Treated mice were evaluated for blood biochemistry, tissue histopathology, and fibrosis markers. Macrophages were isolated from the peritoneal cavity for coculturing with tubular epithelial cells (TECs) and flow cytometry analysis. Key Findings. We found that fibrosis and kidney function loss after IRI were significantly alleviated in Mac IKKα-/- mice compared with wild-type (WT) mice. The expression of fibrosis markers and the infiltration of M2 macrophages were decreased in the kidneys of Mac IKKα-/- mice after IRI. The in vitro experiment showed that the IRI TECs cocultured with IKKα-/- macrophages (KO MΦs) downregulated the fibrosis markers accompanied by a downregulation of Wnt/β-catenin signaling. Significance. These data support the hypothesis that IKKα is involved in mediating macrophage polarization and increasing the expression of fibrosis-promoting inflammatory factors in macrophages. Therefore, knockdown of IKKα in macrophages may be a potential method that can be used to alleviate the AKI-to-CKD transition after IRI.